2004
DOI: 10.1016/j.jtcvs.2003.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Locally applied cilostazol suppresses neointimal hyperplasia by inhibiting tenascin-C synthesis and smooth muscle cell proliferation in free artery grafts

Abstract: A single topical administration of cilostazol may suppress neointimal hyperplasia by inhibiting cell proliferation and tenascin-C synthesis in free artery grafts, presenting the potential for clinical use in vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…In the aortic segments donated by WT mice (WTNWT and WTNTN− groups), the changes in the distribution of TNC expression during the first 28 days after surgery, which seemed to shift from the media to the neointima, were similar to those previously observed in free artery grafts in rats [17]. By contrast, in the grafts donated by TN− mice transplanted to WT mice (TN−NWT group), the expression of TNC protein was detected only in the neointima, and was associated with the emergence of predominant α-SMA positive cells.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In the aortic segments donated by WT mice (WTNWT and WTNTN− groups), the changes in the distribution of TNC expression during the first 28 days after surgery, which seemed to shift from the media to the neointima, were similar to those previously observed in free artery grafts in rats [17]. By contrast, in the grafts donated by TN− mice transplanted to WT mice (TN−NWT group), the expression of TNC protein was detected only in the neointima, and was associated with the emergence of predominant α-SMA positive cells.…”
Section: Discussionsupporting
confidence: 76%
“…Careful observation also suggests that some TNC-producing cells may directly migrate from recipient vessels into the neointima of grafts across the anastomosis. In vascular lesions, several types of cells including SMCs [8,17], fibroblasts [37], myofibroblasts [38], and endothelial cells [39] have been reported to express TNC protein. The double staining of LacZ and α-SMA showed that TNC-producing cells were positive for α-SMA in both the TN+/−NWT and WTNTN+/− groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cilostazol inhibits phosphodiesterase III preventing tenascin-C expression by vascular smooth muscle cells during neointimal hyperplasia. 25,26 AT-1 antagonists and ACE inhibitors could also be useful since they inhibit angiotensin II, which is a potent inducer of tenascin-C. These drugs were shown to block vascular tenascin-C expression in hypertensive patients.…”
Section: Blocking Tenascin-c Inducing Signaling With Inhibitory Drugsmentioning
confidence: 99%